Un mécanisme de prospective technologique en prospective - Voyer, R. (L'Actualité économique, 1975)
The growth of consumer and environmentalist movements in recent years has shown that technological innovation is not always beneficial. Growing public pressure for better assessments of the consequences of technological projects has lead to the development of the concept of "Technology Assessment" which has been defined as "taking a purposeful look at the consequences of technological change".The concept of "Technology Assessment" originated in the U.S.A. in the early 1960's. In 1972 the Office of Technology Assessment (OTA) was formed as an aid to Congress. However since the Canadian political system differs significantly from that in the U.S.A. a different mechanism for Technology Assessment is needed in Canada. The present paper describes such a mechanism.